The Emotional Battle of The Sexes Game: Psychological Game Theory Applied to the Choice of Tourism - Jose M. Mas; Dr. Anett Erdmann; Dr. Kathrin Jaszus (Tourism and Hospitality Management)
Purpose - Beach or mountain? This study focuses on the complex decision-making process travelers face when choosing a destination, highlighting the significant but understudied role of emotions in destination choice, particularly how emotional expectations influence tourism evaluation. The aim is to derive insights for a strategic choice of image positioning. Methodology, Design, and Approach - Using psychological game theory, the study examines the emotional responses of German tourists in their choice of tourism type on the Balearic Islands, through neuromarketing techniques (EEG, SCR, HVR) and a value assessment survey. This approach models tourists’ decision-making processes in response to visual stimuli, incorporating perceived value and an “emotional care” parameter that accounts for the desire to meet the expectations of travel companions. Results - The study reveals clear differences between equilibria based on purely self-reported value judgments and those incorporating neural responses, highlighting the complexity of emotional influences on travel decisions. Originality - This research contributes to the field of tourism by detailing the interplay between emotional expectations, consideration, and trade-offs in travel decisions. It provides insights for the development of tailored marketing strategies that address emotional needs in order to increase satisfaction in shared travel decisions.